Bioregulatory correction of disorders in humans from seasickness - E.V. Moiseenko; S.-A.I. Madyar; S.V. Chorny; E.E. Kovalevskaya (Ukrainian Antarctic Journal, 2014)
This is a study of human psychophysiological functions at kinetosis from seasickness and the development of a new non-invasive technique bioregulatory correction. Studies were carried out with the participation of Antarctic winterers (23 men aged 25–45 years) during sea passage through the storm Drake Passage. The results of electroencephalographic studies and testing of personal color preferences testified about the importance of psycho-emotional component in the mechanism of occurrence kinetoses from the seasickness. The possibility of correcting the negative effects of kinetosis confirmed by objective data normalization of EEG sessions under the influence of color influence the principle of biofeedback. It is shown that the dominant positive impact on the psycho-emotional state of a person at sea kinetosis inherent chromaticity green and light green spectrum that can affect the capacity of structural reorganization of EEG rhythms and cause expression of the activity of the alpha rhythm.